If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(2c + -7) + 16 = 2(4c + -1) + 8 Reorder the terms: 6(-7 + 2c) + 16 = 2(4c + -1) + 8 (-7 * 6 + 2c * 6) + 16 = 2(4c + -1) + 8 (-42 + 12c) + 16 = 2(4c + -1) + 8 Reorder the terms: -42 + 16 + 12c = 2(4c + -1) + 8 Combine like terms: -42 + 16 = -26 -26 + 12c = 2(4c + -1) + 8 Reorder the terms: -26 + 12c = 2(-1 + 4c) + 8 -26 + 12c = (-1 * 2 + 4c * 2) + 8 -26 + 12c = (-2 + 8c) + 8 Reorder the terms: -26 + 12c = -2 + 8 + 8c Combine like terms: -2 + 8 = 6 -26 + 12c = 6 + 8c Solving -26 + 12c = 6 + 8c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-8c' to each side of the equation. -26 + 12c + -8c = 6 + 8c + -8c Combine like terms: 12c + -8c = 4c -26 + 4c = 6 + 8c + -8c Combine like terms: 8c + -8c = 0 -26 + 4c = 6 + 0 -26 + 4c = 6 Add '26' to each side of the equation. -26 + 26 + 4c = 6 + 26 Combine like terms: -26 + 26 = 0 0 + 4c = 6 + 26 4c = 6 + 26 Combine like terms: 6 + 26 = 32 4c = 32 Divide each side by '4'. c = 8 Simplifying c = 8
| 8*4n-1= | | -68=-4x+5(-x-8) | | 5x+6+8x=5+8x-3x-20-3 | | 3x+25-100=0 | | 60q+45r+75s-180=15(4q+3r+5s+11) | | -68=-4x+5 | | 5x+6+8=5+8x-3x-20-3 | | -3x+5(x-27)=-119 | | (8-z)(4z+6)=0 | | -9-3x=2x+9 | | 5x+6+8=5+8x-3-20-3 | | 37z+43=z+6(6z+5) | | 4k+2k=24 | | n-7-6=-9 | | (4z+7)/(z-19)=83/(z-19) | | -3-7a-7a=-17 | | 7x+8=13y+20 | | -5+x/-2=-2 | | 6m-6-2=22 | | (4z+7)/(z-19)=415/(5z-95) | | 7a-2+7a=12 | | 5a^2-2ab-16b^2= | | 31-x=43 | | -p+3p=-2 | | 42=5(x+8) | | -6x+1-6=1 | | 21y-49= | | .05x+.33-.75x+0.6666666667-0.8333333333x=8-1.4 | | 3.18-4=8.72 | | 2/3s=18 | | 11-10x=42x+19 | | 6x+11=-79-9 |